Continuous Complete Remission in Two Patients with Acute Lymphoblastic Leukemia and Severe Fungal Infection Following Short-Term, Dose-Reduced Chemotherapy - Florian Lüke; Dennis C. Harrer; Joachim Hahn; Matthias Grube; Tobias Pukrop; Wolfgang Herr; Albrecht Reichle; Daniel Heudobler (Frontiers Media S.A., 2021)
Spontaneous remission in acute lymphoblastic leukemia (ALL) is a rare phenomenon, which typically involves a pattern of feverish or septic disease followed by quick but mostly transient remission. We report on two male patients (46-year-old (pt. 1) and 19-year-old (pt. 2)) with CD20 positive, BCR-ABL negative common B-ALL. Patient 1 had received dexamethasone and cyclophosphamide (1.2 g) as a prephase therapy, followed by rituximab and a cumulative dose of 200 mg daunorubicin combined with 2 mg vincristine as an induction therapy. Patient 2 was treated with a reduced therapy regimen (Vincristine 1 mg, dexamethasone and 80 mg daunorubicin, 12-month mercaptopurine maintenance) due to (alcohol-related) toxic liver failure and pontine myelinolysis. Both patients developed severe septic disease just few days into induction treatment. Patient 1 suffered from pulmonary mycosis, which had to be resected eventually. Histological work-up revealed invasive mucor mycosis. Patient 2 presented with elevated serum aspergillus antigen and radiographic pulmonary lesions, indicative of pulmonary mycosis. In both patients, chemotherapy had to be interrupted and could not be resumed. Both patients recovered under broad antimicrobial, antifungal and prophylactic antiviral therapy and achieved molecular complete remission. At data cut-off remissions had been on-going for 34 months (pt. 1) and 8 years (pt. 2). Short-term, reduced intensity induction chemotherapy accompanied by severe fungal infections was followed by long-lasting continuous complete remissions in ALL. Thus, we hypothesize that infection-associated immunogenic responses may not only prevent early relapse of ALL but could also eradicate minimal residual disease. The effects of combined cytotoxic therapy and severe infection may also be mimicked by biomodulatory treatment strategies aiming at reorganizing pathologically altered cellular signaling networks. This could reduce toxicity and comorbidity in adult patients requiring leukemia treatment. Therefore, these two cases should encourage systematic studies on how leukemia stroma interaction can be harnessed to achieve long lasting control of ALL.